When do patients with Tetralogy of Fallot need a transannular patch. Issue 12 (15th November 2022) - Wang, Zhangwei; Li, Zhiqiang; Ding, Nan; Zhu, Yaobin; Li, Xiaofeng; Yi, Hanlu
Abstract: Objectives: The objective of this study was to evaluate the predictive value of main pulmonary artery (MPA) Z  score, pulmonary valve annulus (PVA) prop, great aortic valve annulus (GA) ratio, PVA index (PAI), and PVA area index (PAAI) indicators in patients with Tetralogy of Fallot (TOF) and whether or not to undergo transannular patch (TAP). Methods: A retrospective analysis was performed on the clinical data of 263 patients with TOF who underwent radical operations from 2010 to 2021 at Beijing Children's Hospital. Sixteen cases were excluded, and 247 cases (male/female = 155/92) were included in this study. Based on whether TAP was selected intraoperatively, the patients were divided into the TAP group (82/247) and the non‐TAP group (165/247). The diameter of the PVA, the aortic valve annulus, and the MPA were measured by echocardiography, and the PVA Z  score, MPA Z  score, PVA prop, GA ratio, PAI, and PAAI indexes were calculated, and statistical analysis was carried out. Results: The PVA Z  score, MPA Z  score, PVA prop, GA ratio, PAI, and PAAI of the TAP group were lower than those of the non‐TAP group ( p  < .0001, p  < .0001, p  < .0001, p  < .0001, p  < .0001, and  p  < .0001). Receiver‐operating curve analysis showed that the cut‐off value of PVA Z  score was −1.96 (area under the curve [AUC]: 0.822; 95% confidence interval [CI]: 0.769–0.874); the cut‐off value of MPA Z  score was −1.04 (AUC: 0.778; 95% CI: 0.711–0.845); the cut‐off value of PVA prop was 0.37 (AUC: 0.812; 95% CI: 0.751–0.874); the cut‐off value of GA ratio was 0.64 (AUC: 0.812; 95% CI: 0.750–0.874); the cut‐off value of PAI is 0.78 (AUC: 0.812; 95% CI: 0.750–0.874); and the cut‐off value of PAAI is 0.4 (AUC: 0.812; 95% CI: 0.750–0.874). Pulmonary valve bicuspid malformation is one reason why predictive models fail to predict the possible avoidance of TAP. Pearson's correlation and linear regression analysis showed that PAI had the strongest correlation with PVA Z  score, followed by that between PVA prop and PVA Z  score, and the weakest correlation between PAAI and PVA Z  score. Conclusions: PVA prop, GA ratio, PAI, and PAAI can well predict TAP selection, and the measurement is simple and convenient. Compared with PVA Z  score, they are not hindered by other confounding factors, and can well replace the application value of PVA Z  score in TAP prediction. The predictive efficacy of PAI and PVA prop is numerically better than the GA ratio, and PAAI, PAI, and PVA prop combined with MPA Z  score can improve the predictive value of PAI and PVA prop, respectively. Although various echocardiographic parameters can be used as indicators to predict surgical approach in patients with TOF, PV morphology and tissue characteristics should also be considered.